Museum cooperation between Africa and Europe: a new field for museum studies: edited by Thomas Laely, Marc Meyer and Raphael Schwere, Kampala, Fountain Publishers/Bielefeld, Transcript Verlag, 2018, 240 pp., $40.00 USD (paperback), ISBN 978-8376-4381-7. - Chipangura, Njabulo (Museum Management & Curatorship, 2020)
This book ushers in a very important contribution and comes at a time of debates on how decoloniality can be empirically approached within African museum practice. Whereas national museums in Africa are still conceived of as offshoots of the colonial legacy, community museums have managed to give priority to social aspects by providing a meeting place where cultural identities of a particular community are revitalised. In many ways, this chapter seems to be pointing out the idea that community museums provide an empirical illustration of how the museum practice in Africa can be decolonised.